2021
DOI: 10.1016/j.trecan.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming in Anticancer Drug Resistance: A Focus on Amino Acids

Abstract: Overcoming anticancer drug resistance is a major challenge in cancer therapy, requiring innovative strategies that consider the great tumor heterogeneity and adaptability. Here we provide recent evidence highlighting the key role of amino acid (AA) metabolic reprogramming in cancer cells and the supportive microenvironment in driving resistance to anticancer therapies. AAs sustain the acquisition of anticancer resistance by providing essential building blocks for biosynthetic pathways and for maintaining a bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 158 publications
1
37
0
Order By: Relevance
“…The presently observed high GSH levels indicate that GSH is not depleted by cisPt in cells with chronic cisPt exposure. Moreover, GSH is still provided in excess in cells a long time after suspension of chronic exposure reflecting cellular adaptation and metabolic reprogramming for maintaining the intracellular redox-balance [26]. In agreement with the current findings, significantly elevated GSH levels were recently reported in cisPt resistant ovarian A2780 cancer cells compared to the non-resistant parental cell line.…”
Section: Glutathione (Gsh)supporting
confidence: 91%
“…The presently observed high GSH levels indicate that GSH is not depleted by cisPt in cells with chronic cisPt exposure. Moreover, GSH is still provided in excess in cells a long time after suspension of chronic exposure reflecting cellular adaptation and metabolic reprogramming for maintaining the intracellular redox-balance [26]. In agreement with the current findings, significantly elevated GSH levels were recently reported in cisPt resistant ovarian A2780 cancer cells compared to the non-resistant parental cell line.…”
Section: Glutathione (Gsh)supporting
confidence: 91%
“…In addition, intercellular or subcellular transportation of amino acids and altered metabolism induced by overexpression of amino acid transporters support cancer cell metabolism overcoming drug-induced stress [ 7 , 8 ]. Growing evidence indicates that suppressing or enhancing amino acid metabolism and depletion or supplementation of amino acid availability is effective in abolishing drug resistance in cancer cells [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells reprogram their amino acid metabolisms to sustain tumor progression, then carry out specific strategies of resistance to anticancer therapies. 32 In this study, the potential metabolic pathways related to chemoresistant status showed typical metabolic pathways including biosynthesis of phenylalanine, tyrosine and tryptophan, phenylalanine metabolism as well as purine metabolism were participated in the process of K562 chemoresistance.…”
Section: Discussionmentioning
confidence: 77%